Analysis of the Implementation of the Teacher Learning Day Program (PHBG) in Improving Teacher Competence - Lanniari Siregar; Nini Aryani; Nopa Wilyanita (Global Education Journal, 2026)
This study aims to analyze the implementation of the Teacher Learning Day Program (PHBG) in improving the pedagogical competence of early childhood education (ECE) teachers in the Drupadi Cluster, Dayun District. This study employed a qualitative approach with a descriptive method. The research subjects consisted of 14 ECE teachers who are members of the Drupadi Cluster. Data were collected through interviews, observations, and documentation. The results of the study indicate that the implementation of PHBG has a positive impact on improving teachers’ pedagogical competence. Teachers have become more capable of creating a safe and comfortable learning environment, designing and implementing student-centered learning, conducting assessments of children's development, utilizing simple technology in learning, as well as engaging in reflection and professional collaboration. In addition, PHBG activities also help teachers in developing students' potential according to the characteristics of early childhood. Based on these findings, it can be concluded that the Teacher Learning Day Program (PHBG) plays an important role in improving the pedagogical competence of ECE teachers in the Drupadi Cluster, Dayun District, and can serve as an effective strategy for continuous teacher professional development.